(1325) impact of American foreign trade on smaller economies تأثير التجارة الخارجية الأمريكية على الاقتصادات الأصغر - montasser, saadia H. (The Institute Of National Planning., 2018)
In a large economy like the American economy with total imports a small proportion of output it is expected a prior that major sources of inflation would be domestic rather than imported» It is further expected that the increase in domestic cost items would be to the effect of exporting inflation to the rest of the world with small economies doing sizable trade with the States affected the most.